2022
DOI: 10.1002/joom.1206
|View full text |Cite
|
Sign up to set email alerts
|

Globally distributed technology projects thrive on experience working together apart: Impacts of team balance, task balance, and task heterogeneity

Abstract: Enabling shared experiences could be key to managing technology projects successfully. The advantages gained from the experience of working together can be complemented, but also offset, by common aspects of technology projects—like the dispersion of team members and the integration of heterogeneous tasks across global sites. This study develops and tests a conceptual framework that scrutinizes the impact of team familiarity and task allocation challenges. It identifies three elements of task allocation in tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…To accommodate the potential endogeneity bias, we used an instrumental‐free method using the Gaussian Copula approach (Park & Gupta, 2012). Consistent with prior studies (Alblas, 2022; Salvador et al, 2021), we first conducted a Shapiro–Wilk test to assess whether the endogenous regressor (e.g., group technology workarounds) is non‐normally distributed. The results of this test indicated that the endogenous regressor was non‐normally distributed ( W = 0.938, p < .001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accommodate the potential endogeneity bias, we used an instrumental‐free method using the Gaussian Copula approach (Park & Gupta, 2012). Consistent with prior studies (Alblas, 2022; Salvador et al, 2021), we first conducted a Shapiro–Wilk test to assess whether the endogenous regressor (e.g., group technology workarounds) is non‐normally distributed. The results of this test indicated that the endogenous regressor was non‐normally distributed ( W = 0.938, p < .001).…”
Section: Methodsmentioning
confidence: 99%
“…Although various task characteristics have been investigated in the extant OM literature (Alblas, 2022; Pagell & LePine, 2002), we focus on task nonroutineness because it has a high level of theoretical and practical relevance. First, task nonroutineness includes task (un)analyzability and variety, reflecting the extent to which the tasks are not routine or understandable (Majchrzak et al, 2005; Perrow, 1967).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…The literature above suggests that BDA can impact KS (Sleep et al, 2023) which can influence PS (Alblas, 2022). Hence, the following hypothesis is proposed: H7: KS mediates the relationship between BDA and PS.…”
Section: Based On the Arguments It Is Proposed Thatmentioning
confidence: 98%
“…Projects frequently involve complex tasks requiring various skills and knowledge; effective knowledge sharing can help ensure that all participants can access the information and resources they need to complete and provide the PS (Ahlfänger et al, 2022). By exchanging knowledge, team members can avoid duplicating efforts, gain insight from one another's experiences, and work collaboratively to solve problems and surmount obstacles (Alblas, 2022). This can assist in enhancing work quality and decreasing errors and increasing the project's success.…”
Section: The Mediating Role Of Knowledge Sharingmentioning
confidence: 99%